Economic Reform in Hungary Since 1968 - Somogyi, Janos (Occasional Papers; Occasional Paper, 1991)
This paper examines Hungary's reforms since 1968. It discusses the government's medium-term adjustment program, unveiled in the fall of 1990, which aims to install the key elements of a market economy in three years.